INCOTERMS COMPARISONS BETWEEN SEA AND LAND : CASE STUDY OF EXPORT BAGGED SUGAR - Rungsuwannarat, Paveena (Journal of Graduate School of Commerce-Burapha Review, 2020)
The objective of this research is to propose the cost and the factor which is choose for sell and buy incoterm comparison between sea and land for the shipper sugar mill and distributor was selected for this study, Methodology use primary data the cost for Sea freight and Land Freight from Thailand to Cambodia Second, Cost Analysis comparison between Sea freight and land Freight and interview 16 people with seller and buyer who can make a decision to choose and can use incoterms. Respectively, After comparison the cost incoterm found out that Sea Freight save cost more than Land Freight and the factor mostly opinions is Buyer’s responsibility and sugar sale system. Although Seller can make profit from freight rate if they change the incoterm to be CFR and CIF but the seller still not change to sell for another term due to company policy, Convennience caused, Release product, internal company logistic and place of destination. In the Meantime the buyer required to buy another incoterm they want seller ease burder even have to pay.